On the Design of Adaptive Educational Hypermedia Systems - Retalis, Symeon; Paraskeva, Fotini; Papasalouros, Andreas; Tzanavari, Aimilia (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
Adaptive Educational Hypermedia Applications (AEHA) are gaining the focus of the research and development community as a means of alleviating a number of user problems related to hypermedia and web-based education (e.g. “lost in hyperspace”, cognitive overload, guidancementoring, etc.).